Clinical Characterization of Atypical Primary Progressive Aphasia in a 3-Year Longitudinal Study: A Case Report. Issue 3 (2nd September 2021) - Basilico, Stefania; Ciricugno, Andrea; Gelosa, Giorgio; Magnani, Francesca G.; Mosca, Lorena; Popescu, Cristina; Garibotto, Valentina; Sberna, Maurizio; Paulesu, Eraldo; Bottini, Gabriella
Abstract : The logopenic variant of primary progressive aphasia (lvPPA) is the most recent variant of primary progressive aphasia (PPA) to be identified; thus far, it has been poorly investigated. Despite being typically associated with Alzheimer disease (AD), lvPPA has recently been linked to frontotemporal lobe degeneration (FTLD), with distinctive cognitive and neural features that are worthy of further investigation. Here, we describe the neuropsychological and linguistic profile, as well as cerebral abnormalities, of an individual exhibiting PPA and carrying a pathogenetic variant in the GRN gene, from a 3-year longitudinal perspective. The individual's initial profile resembled lvPPA because it was characterized by word-finding difficulties and phonological errors in spontaneous speech in addition to sentence repetition and phonological short-term memory impairments. The individual's structural and metabolic imaging data demonstrated left temporal and bilateral frontal atrophy and hypometabolism, respectively. On follow-up, as the pathology progressed, dysprosody, stereotypical speech patterns, agrammatism, and orofacial apraxia appeared, suggesting an overlap with the nonfluent variant of PPA (nfvPPA). Severe sentence comprehension impairment also became evident. Our longitudinal and multidisciplinary diagnostic approach allowed us to better characterize the progression of a GRN -positive lvPPA profile, providing neuropsychological and imaging indicators that might be helpful to improve classification between different PPA variants and to address a nosological issue. Finally, we discuss the importance of early diagnosis of PPA given the possible overlap between different PPA variants during the progression of the pathology.